Bactericidal effects of diluted slightly acidic electrolyzed water in quantitative suspension and cabbage tests. (December 2021) - Yoon, So-Ra; Lee, Jae Yung; Yang, Ji-Su; Ha, Ji-Hyoung
Abstract: Slightly acidic electrolyzed water (SAEW) is an effective disinfectant used to control food poisoning bacteria. In this study, we evaluated the sterilization effect of an SAEW stock solution and 5–90% SAEW solutions, and the potential for bacterial reactivation after disinfection. SAEW stock solution at ACC of 31.2 ± 0.22 mg/L, pH of 5.51 ± 0.01, ORP of 895 ± 6 mV for disinfection effect assessment was used. SAEW at a concentration of 40% resulted in a >6 log reduction in Yersinia enterocolitica in a suspension test and on cabbage. Analysing the bactericidal efficacies of 5–90% SAEW indicated that a concentration of >70% SAEW thoroughly eliminated Y. enterocolitica . Additionally, SAEW-sterilized cabbage was stored at 5 °C, 10 °C, 20 °C, and 30 °C for one week to investigate the resilience of the damaged bacteria. Following the disinfection with 40% SAEW, cabbage must be stored at a low temperature of <10 °C to prevent the regrowth of Y. enterocolitica . The results from this study support the use of >70% SAEW and indicate that the storage temperature of cabbage following the disinfection and washing are important for ensuring food safety. Highlights: Diluted slightly acidic electrolyzed water (SAEW) is an effective disinfectant. The oxidation reduction potential of the SAEW dilution was related to efficacy. SAEW (40%) resulted in a >6 log reduction, and >70% SAEW eliminated Y. enterocolitica. For 40% SAEW, cabbage must be stored at <10 °C to prevent bacterial reactivation.